Prevention and Management of Stress Ulcers in Critically ill Patients - Zulfakhri, Zulfakhri; Jufan, Akhmad Yun; Wisudarti, Calcarina Fitriani Retno (Perhimpunan Dokter Spesialis Anestesiologi dan Terapi Intensif, 2024)
Stress ulcers or stress related mucosal damage (SRMD) is a term defining inflammation, erosion, and ulceration in the upper gastrointestinal tract complicating patients with critical illness. Stress ulcers occur because of imbalance between the aggressive factors in stomach (gastric acid, pepsin, and bile salt) and the defensive factors (mucous, bicarbonate, microcirculation, epithelial layer, and prostaglandin). The most common clinical feature of stress ulcers is upper gastrointestinal tract bleeding in which the incidence rate is 2.6% in critically ill patients. Stress ulcers commonly happen after a gastrointestinal mucosal break in 75–100% of intensive care unit (ICU) patients in the first 24 hours of admission. The classification of stress ulcers includes asymptomatic stress ulcers, stress ulcers with occult and overt bleeding, and stress ulcers with clinically significant gastrointestinal bleeding. The diagnosis of stress ulcers can be made by assumption only and do not need an endoscopy. Some cases of stress ulcers that need an endoscopy are patients with overt and clinically significant gastrointestinal bleeding stress ulcers. Thus, the treatment of stress ulcers is similar to upper gastrointestinal bleeding. Stress ulcers can be prevented by administering stress ulcers prophylaxis such as histamine H2 receptor antagonist, proton pump inhibitor, cytoprotective agent (sucralfate), and usage of enteral feeding method.